(3GdEOGQI GdYGeI (B/s - (3GdeLOhH, WGQbs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2001)
(3jJfGhd gPG GdcJGH GdEOGQI GdYGeI h GdYedjI GdEOGQjI h GdhXjaI GdYGeI h GdEUdGM GdEOGQj, aeGgjI GdEOGQI GdYGeI JJchf GdOhd`````I ef eLehYI CaQGO JGHYjf dSdWI SjGSjI YdjG h NGVYjf dbhGfjf YGeI eTJQcI(B. (3JQej GdEOGQI GdYGeI, ef LgI, Edi hUa h TQM HfjI h egGe GdCLgRI GdJj jhcd EdjgG egeI JMbjb GdCgOGa PGJ GdeUdMI GdLeGYjI GdeMOOI ef bHd(B.s
Keywords: (3GdEOGQIs; (3GdGOGQI GdYGeIs